Sorption of Lead(II) in Aqueous Solution on Chitin - Xiong, Chunhua (Asian Journal of Chemistry, 2010)
The present research was aimed at the development of chitin as an adsorbent that it can be used in the removal of lead(II) ions to obtain equilibrium, kinetics and thermodynamic parameters. The experimental results show that the optimal pH for the sorption of lead(II) ions was 6.72 in the CH3COOH-CH3COONa system and the maximum adsorption capacity was estimated to 44.0 mg g-1 chitin by saturated capacity method. The apparent sorption rate constant was k298K = 2.70 × 10-5 s-1. Experimental results were found to fit to Freundlich isotherm model over the entire studied concentration range. Effect of temperature on the equilibrium distribution values has been studied to evaluate the changes. The thermodynamic parameters, ΔG298K was calculated to be -16.1 kJ mol-1, ΔH and ΔS were found to be 13.1 kJ mol-1 and 97.8J mol-1 K-1 and the results show that the adsorption was feasible, spontaneous and endothermic under examined conditions. Adsorption mechanism was also proposed for the adsorption of lead(II) ions onto chitin using infrared spectroscopy technique.